PENGARUH PENGATURAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA PEGAWAI PADA BAGIAN PEMBANGUNAN KANTOR WALIKOTA SAMARINDA - Julita, Risca (PREDIKSI, 2012)
The purpose of this study was to determine the effect of setting the working environment of the employees working spirit in Samarinda Mayor's Office of Development.The results showed that a positive work environment settings on employee discipline in Samarinda Mayor Office of Development.It can be proved that the value of rxy coeffeicient corelasi or r count equal to 0.411, while the value of r or r product moment of decision tables in alpha significance level of 0.05 or 5% N = 25-1 is r 0, 05, 24 = 0.404. Because the value of r xy> r table (0.411> 0.404),. Oleh karena nilai r xy > r tabelÂ (0,411 > 0,404), Because the value of r xy> r table (0.411> 0.404), it can be said that the Working Environment variable settings have a significant effect on the Employee Morale Development Section Samarinda Mayor Office, the research hypothesis is thus accepted..More Proof the output results obtained tcount table coeficient of 5.800. In the t distribution table with a 0.05 significance level decision or 5% of the value obtained TTable or t 0.05, 24 = 1.708. Because thitung> ttable or (5.800>1.708) then so the hypothesis.